Effectiveness of cooperative credit for agricultural production - National Council of Applied Economic Research (New Delhi : National Council of Applied Economic Research, 1972)
This study is a somewhat extended case study of selected agricultural cooperative credit societies in three districts, one in Gujarat, one in Mysore, and one in Bihar
Includes index
osc 26/03/2019
Loans
Keywords: Agricultural cooperative credit associations